The Importance of the Structure and Content Analysis of the Exit Interview in Companies for the Success of its Implementation - Lana Milivojević (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The exit interview is a valuable tool for companies through which they can learn valuable information related to work processes, along with information’s about employees and the reasons for leaving the company, as well as potential or real security and reputational threats (outflows of business secrets, bad business practices, etc.) that companies may suffer or suffer damage. That is why this type of interview is very important, and often neglected in practice or conducted with insufficient quality. For this reason, this paper considers the importance of the structure and analysis of the content of the exit interview in companies for the success of this type of interview. When conducting exit interviews in companies, these interviews should certainly be structured, so the paper explains in detail and with examples all phases of a structured interview, starting with the phase of planning and preparation for conducting an exit interview, the introductory phase, the phase of free expression (thinking), the phase of asking questions, the final phase of the exit interview and the evaluation phase of the exit interview. Special attention was paid in the work to the preparation of the exit interview and the compilation of a written interview plan according to its phases, as well as asking relevant questions. Valuable insights gained from the exit interview are used in the improvement of business processes and can and should certainly be used when deciding on further employment in the company. Due to the multiple importance of conducting the exit interview, the paper also pointed out the security aspect of its conduct. Also, for the success of the exit interview, the assessment of the credibility of the content of such an interview, that is, the employee's statement, is important, which requires knowledge of verbal and non-verbal indicators of lying, some of the more significant of which are briefly discussed in this paper.